2005
DOI: 10.1152/physiolgenomics.00197.2004
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mouse model TallyHo carries an obesity gene on chromosome 6 that exaggerates dietary obesity

Abstract: The TallyHo (TH) mouse strain is a polygenic model for Type 2 diabetes with obesity. Genetic analysis in backcross progeny from a cross between F1 [C57BL/6J (B6) x TH] and TH mice mapped a quantitative trait locus (QTL) named TH-associated body weight 2 (tabw2) to chromosome 6. The TH-derived allele is associated with increased body weight. As a first step to identify the molecular basis of this obesity QTL, we constructed a congenic line of mice on the B6 genetic background that carries a genomic region from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 72 publications
3
35
0
Order By: Relevance
“…For example, Bwq2 [24] and Tabw2 [8] apparently overlap with Bwdq2 and Obdq1 on chromosome 6. We previously identified Bwq2 as a modifier QTL for the A y allele in an F 2 intercross between B6 and obese KK-A y strains [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bwq2 [24] and Tabw2 [8] apparently overlap with Bwdq2 and Obdq1 on chromosome 6. We previously identified Bwq2 as a modifier QTL for the A y allele in an F 2 intercross between B6 and obese KK-A y strains [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…TallyHo mice represent a newly defined polygenetic model of Type II diabetes and are characterized by hyperglycemia, hyperinsulinemia, hyperlipidemia, and moderate obesity (23,24,52). It has been suggested that TallyHo mice may be more representative of the polygenic nature of Type II diabetes in humans (23).…”
mentioning
confidence: 99%
“…With respect to QTLs for leptin in obese mice, Kim et al [10] reported a similar result. A congenic mouse strain B6.TH-tabw2/tabw2, which carries obesity QTL tabw2 from the obese TallyHo mouse strain, had increased plasma leptin concentrations compared with control B6.TH-+/+ mice.…”
Section: Females (N=298) C) Reference Map Position (Cm) Was Retrievementioning
confidence: 74%